On the algorithm for adaptive noise canceller with parallel block structure - Kidakorn, P.; Rattanakoch, W.; Kimpan, C.; Pin-Ngern, Ouen; Noppanakeepong, S. (My University, 2002)
An adaptive algorithm for detecting a single sinusoid of unknown frequency corrupted by Gaussian noise was proposed by Nishimura et al. (Trans. IEICE, vol. J72-A, no. 5, pp.786-794, 1989) using a IIR band pass filter with a variable center frequency and parallel block structure for fast processing. In 1996 an adaptive algorithm was investigated which solved the problem whereby the presence of several input frequencies led to the situation of it being impossible to achieve convergence using the new algorithm proposed by Takahashi et al. (Proc. IEEE APCCAS'94, pp. 376-381, 1994). However, the control signal generated by the new algorithm, used for adjusting the center frequency of the band pass filter, still jitters in spite of its convergence. In this paper, in addition to using the output in an adaptive algorithm as proposed, the input signal is used as an auxiliary or reference signal. In this way the jitter on the control signal can be reduced significantly, with the same convergence rate, with little added computational complexity.
Keywords: Adaptive algorithm; Adaptive filters; Band pass filters; Convergence; Digital filters; Frequency; Gaussian noise; Noise cancellation; Programmable control; Signal generators